Black expression and white generosity : a theoretical framework of race - Wall, Natalie (Emerald Publishing Limited, 2024)
"Ungrateful." An accusation that will be instantly familiar to non-white people throughout majority-white states, levelled by everyone from online trolls to government ministers. Despite a centuries-old colonial history of exploitation, displacement, and enslavement, whiteness continues to construct itself as generous and benevolent: the brave liberators of slaves rather than their captors; the recipients of immigrants to their great lands rather than perpetrators of racist hate crimes; the protectors of the marginalised rather than the perpetrators of oppression. In Black Expression and White Generosity: A Theoretical Framework of Race, Natalie Wall takes readers on a journey through the tropes and narratives of white generosity, from the onset of the African slave trade to contemporary efforts to ridicule and undermine the "woke agenda." She offers a theoretical framework for use by antiracist scholars, students, and activists to name and interrogate this pervasive attitude and its role in the structures of white supremacy and in the continued marginalisation of non-white people. Providing an exploration of lived experience and of the theoretical underpinnings of that lived experience, Wall offers a new vocabulary with which to speak truth to power and decentre whiteness from the work of antiracism, by looking to moments of black expression and creativity in black arts production. Taking inspiration from the bold, powerful, and experimental work of black artists and activists, Black Expression and White Generosity forges an alternative narrative that strives for freedom and justice without relinquishing anything in return. It is your indispensable guide to remaining ungrateful.
Keywords: Ingratitude.; Black people -- Social conditions.; Black people -- Political activity.; Activism.; Social Science, Activism & Social Justice.; Racism and racial discrimination, Anti-racism.; Political activism -- Political engagement.; Social discrimination and social justice.; elektronické knihy; electronic books